A Finite Element Method using COMSOL on ERT Applying Metal Wall Pipe: Effect on the Potential Distribution and Current Streamline - Suzanna Ridzuan Aw; Ruzairi Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Yasmin Abdul Wahab; Zulkarnay Zakaria; Nurainizzati Shuhaimi; Farah Hanan Azimi; Lia Safiyah Syafie; Damhuji Rifai; Juliza Jamaludin (MyCT Publishers, 2024)
Non-Indexed Publication